Empathic Knowledge Management: reverse simulation experiments in a learning laboratory. (21st March 2008) - Behara, Ravi S.; Thatchenkery, Tojo; Kenney, Con
The effective management of knowledge has emerged as a critical competency for organisations. This paper presents a methodology for managing knowledge in information- and knowledge-intensive services. The Empathic Knowledge Management methodology was developed on the foundation of an appreciative inquiry framework that surfaces and utilises tacit knowledge of participants in the context of process design efforts in a learning laboratory environment. Behavioural and analytic interventions were used to elicit and formalise the knowledge of the participants. The behavioural interventions created and maintained a learning climate for reverse simulation using appreciative inquiry, while the analytic interventions included systemic problem formulation, service blueprint development and system specification using appropriate software tools. The methodology was tested successfully in the design of two distinct product delivery processes in a large financial services company in the USA.